Financial intermediaries and economic growth: evidence from emerging markets - Biswas, Joydeep (2008)
Does the market-oriented "finance leads to economic growth" strategy have any merit in the emerging markets? This paper studies the effect of stock market and banking sector development on economic growth in 10 emerging economies. using Granger-causality tests, the present study finds little evidence of a causal relationship going from stock market development to economic growth. Findings of the present study show that for most of the emerging markets there are unidirectional and/or bi-directional causality that runs from economic growth to financial sector. - Reproduced.
Keywords: Financial markets; Economic growth